2005
DOI: 10.1016/j.jvs.2005.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative approach to endotension

Abstract: Endotension after EVAR may cause subsequent aneurysm rupture. Endotension is evidently not associated with endoleak I to III provided that the endovascular graft is maintained in appropriate position and that free endovascular flow is observed. We propose to consider a nonoperative approach in the clinically asymptomatic patient with aneurysm enlargement after EVAR if endoleak is excluded by well-performed imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 20 publications
0
53
0
1
Order By: Relevance
“…Mennander et al found five patients (3.1%) with endotension within 160 patients who underwent endovascular aneurysm repair, and endoleaks were not detected. Three suffered aneurysm sac ruptures during the study period, but none of them presented clinical evidence of major bleeding 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mennander et al found five patients (3.1%) with endotension within 160 patients who underwent endovascular aneurysm repair, and endoleaks were not detected. Three suffered aneurysm sac ruptures during the study period, but none of them presented clinical evidence of major bleeding 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Even without any detectable endoleaks, and the aneurysm sac may grow due to endotension or undetectable endoleaks, this aneurysm sac may rupture and cause death. In the event of an aneurysm sac rupture, after a chimney procedure, no endovascular procedure is safe, and open surgery that was once avoided now has a higher risk and is characterized by even greater technical difficulties 3,5,[8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is referred to as endotension; potential etiologies include the presence of a co-existing occult endoleak (Type I, II or III), filtration of blood through the stent-graft fabric or an ineffective barrier to pressure transmission [34,35]. The MDCT finding is progressive expansion of the excluded aneurysm sac (Fig.…”
Section: Type V Endoleaksmentioning
confidence: 99%
“…To date, endoleaks have been classified into 5 different subtypes and types 1-5 are illustrated in (Greenhalgh and Powell 2008) Typically, endoleaks that are classified as type 3 or type 4 resolve spontaneously; however endoleaks classified as type 1 or type 2 often require surgical intervention (Greenhalgh and Powell 2008). Treatment options for type 5 remain controversial as surgeons remain divided on advocating immediate surgical repair versus a more conservative surveillance approach (Mennander et al 2005, Veith et al 2002. Migration of the stent-graft following the EVAR procedure is another complication associated with considerable postoperative morbidity.…”
Section: Complications Associated With Evarmentioning
confidence: 99%